A Case of Parkinson Disease With Both Visual Hallucination and Pain Improved by Gabapentin. Issue 1 (January 2016) - Abe, Kie; Chiba, Yuhei; Katsuse, Omi; Hirayasu, Yoshio
Abstract : Objectives: Visual hallucinations (VHs) and pain are common non-motor symptoms in Parkinson disease (PD). Although dopaminergic dysfunction has traditionally been considered as the principal cause of these symptoms, the detail mechanisms are still unclear. Conventional treatment for VH, decrease of dopamine agonists, and use of antipsychotic medications often lead to an exacerbation of motor symptoms and excessive sedation. Gabapentin (GPT) is an antiepilepsy drug, which affects the glutamic acid neuron system and the γ-amino butyric acid neuron system. It is also known to have an analgesic effect. Here, we report a case of PD in which GPT improved both VH and pain without any adverse effects. Methods: This study is a case report. Results: The subject is an 81-year-old Japanese man who was diagnosed with PD at the age of 67 years. His Hoehn and Yahr staging scale was IV. He developed VH of insects and also experienced pain, which is, as he described, caused by these insects invading his body. Despite the general treatments, VH and pain persisted. Moreover, exacerbation of motor symptoms and excessive sedation hindered a further attempt. Gabapentin was administered to ease his pain. After that, not only pain but also VH disappeared without any adverse effects. Conclusions: The positive outcomes of GPT on VH and pain without any adverse effects may offer us a useful alternative treatment for PD. Further experience and study are needed to prove the efficacy of this agent.